Looking through supply shocks versus controlling inflation expectations: Understanding the Central Bank dilemma - Paul Beaudry; Thomas J. Carter; Amartya Lahiri (Bank of Canada, 2022)
Central banks in most advanced economies have reacted similarly to the increase in inflation that started in 2021. They initially looked through the rising inflation by leaving monetary policy relatively unchanged. Then, after inflation continued to increase, central banks pivoted by quickly tightening monetary policy. The pivot was explained, at least in part, as aiming to anchor drifting inflation expectations. Why might central banks want to look through supply-driven inflation sometimes and pivot away at other times? When does a change in monetary policy stance help anchor expectations? When is a strong monetary policy tightening compatible with a soft landing? In this paper we present a simple environment that helps clarify these issues by offering an optimal policy perspective on recent central bank behaviour. In particular, we examine optimal policy in an environment where there is a risk of wage-price spirals and where the central bank views wage- and price-setters as having bounded rationality. We show how this can provide a coherent explanation of many aspects of recent central bank behaviour.
Keywords: E12; E24; E31; E52; E58; E65; 330; Central bank research; Economic models; Inflation and prices; Monetary policy; Monetary policy and uncertainty; Monetary policy communications